School Strategy For New Students Recruitment In A Private School In Bogor (Case Study at YPHB Senior High School, Bogor) - Andriansyah, Andriansyah; Herfina, Herfina; Irdiyansyah, Iyan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to analyze the strategy of recruiting new students (PPDB) in private schools, especially at YPHB Bogor City High School, the research focuses on: (1) The process of recruiting new students at SMA YPHB Bogor City. (2) Recruitment strategy for accepting new students at SMA YPHB Bogor City in getting prospective students. (3) Factors supporting and inhibiting schools in the recruitment of New Student Admissions (PPDB) at SMA YPHB Bogor City. An effective strategy that can be recommended to be used at YPHB SMA in order to recruit new students every year.The research method used was descriptive qualitative, namely describing, explaining, and disclosing the results of research on student recruitment, with the type of case study research. Data collection techniques included in-depth interviews, participant observations, and documentation. The research subjects were foundations, principals, committees, and parents of students. The results showed that the recruitment strategy for accepting new students at YPHB Senior High School (1) The planning for accepting new students at SMA YPHB was by using internal and external strategies. The internal strategy is carried out through improving school facilities and infrastructure, presenting an attractive school environment. The external strategy is carried out through outreach, placing banners, distributing brochures. Dissemination through social media, print media, electronic media (Publications) on a regular basis. In addition, socialization visits and coordination were also carried out to PPDB target schools. Promotion of YPHB High School flagship programs that can be sold to outside communities so that they can attract more outstanding students. Academic and non-academic Achievement Scholarships and Orphans/Orphans/Orphans with Achievement. Compensation for junior high schools is still being implemented. Holding a PPDB promotional content contest. . (2) The strategy for implementing the recruitment and selection of new students consists of several activities, namely, the establishment of a committee, holding committee meetings for implementing new student admissions, conducting student selection, determining students who are accepted, an announcement of the test results, and re-registration for those who have passed